Nickel-containing factor F430: chromophore of the methylreductase of Methanobacterium. - Ellefson, W L (1982)
The yellow chromophore of the methyl-coenzyme M methylreductase of Methanobacterium thermoautotrophicum has been found to be the nickel-containing factor F430. Treatment of 63Ni-labeled methylreductase with 80% aqueous methanol released the radiolabel as well as the yellow chromophore; both properties were associated with a single compound that was found to be identical to F430, the stoichiometry being 1 mol of nickel per mol of F430 and 2 mol of F430 per mol of methylreductase.